Self-Efficacy in Early Childhood Education and Care: What Predicts Patterns of Stability and Change in Educator Self-Efficacy? - Reyhing, Yvonne; Perren, Sonja (Frontiers in Education, 2021)
Self-efficacy is an important predictor of people’s behaviour and wellbeing. In this longitudinal study we investigated patterns of stability and change in early childhood educator self-efficacy in child-centred educational practice and its predictors. Early childhood educators completed a questionnaire twice. Latent profile analysis yielded four profiles: decrease profile (21.2%), increase profile (25.0%), low profile (9.6%), and high profile (44.2%). Profiles were used as the outcome of a multinomial logistic regression analysis. The analyses showed that educators’ experience, number of hours worked per week, and institution are significant predictors for profile membership: educators with less professional experience and fewer working hours per week have a higher probability of being in the low profile. Family-based educators have a higher probability of being in the decrease profile than centre-based educators. The lack of opportunities to increase self-efficacy available to less experienced, part-time educators and family-based working educators are discussed in frame of Bandura’s (1997) sources of self-efficacy. Practical interventions such as coaching and tandem building are proposed to strengthen educator self-efficacy.